Electromembrane Processes: Experiments and Modelling - Gurreri, Luigi; Tamburini, Alessandro; Micale, Giorgio (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Electromembrane processes offer a multitude of applications, allowing for the recovery of water, other products, and energy. This book is a collection of contributions on recent advancements in electromembrane processes attained via experiments and/or models. The first paper is a comprehensive review article on the applications of electrodialysis for wastewater treatment, highlighting current status, technical challenges, and key points for future perspectives. The second paper focuses on ZSM-5 zeolite/PVA mixed matrix CEMs with high monovalent permselectivity for recovering either acid or Li+. The third paper regards direct numerical simulations of electroconvection in an electrodialysis dilute channel with forced flow under potentiodynamic and galvanodynamic regimes. The fourth paper investigates the reasons for the formation and properties of soliton-like charge waves in overlimiting conditions. The fifth paper focuses on the characterization of AEMs functionalized by surface modification via poly(acrylic) acid yielding monovalent permselectivity for reverse electrodialysis. In the sixth paper, CFD simulations of reverse electrodialysis systems are performed. The seventh paper proposes an integrated membrane process, including electrochemical intercalation-deintercalation, for the preparation of Li2CO3 from brine with a high Mg2+/Li+ mass ratio. Finally, the eighth paper is a perspective article devoted to the acid-base flow battery with monopolar and bipolar membranes.